Method for constructing bionic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium
By 3D printing of porous titanium scaffolding and combining with UV-curable methacrylylated chitosan hydrogel, the problem of mismatch between the elastic modulus of titanium alloy implant and bone tissue and the lack of repairing the microenvironment is solved, achieving efficient Periodontal tissue repair.
Patent Information
- Application Number
- CN202411739895.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-02-18
AI Technical Summary
The existing titanium alloy implants do not match the elastic modulus of bone tissue, and the lack of repair microenvironment, resulting in the failure of repair of periodontal tissue structure.
Porous titanium scaffolds were prepared by 3D printing and microarc oxidation and microwave hydrothermal treatment to form a zinc-containing hydroxyapatite nanowire coating. This is then combined with a UV-curable methacrylylated chitosan hydrogel to form a bionic tissue engineering scaffold.
The matching of the elastic modulus of titanium alloy implant and bone tissue is achieved, inducing new bone formation, and providing an antibacterial repair microenvironment, which improves the success rate of periodontal tissue repair.
Smart Images

Figure CN119455089A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for constructing a bionic tissue engineering scaffold. Background Art
[0002] The technology for repairing the loss of periodontal tissue structure has an urgent need for "scaffold material selection and microenvironment construction". At present, the elastic modulus of titanium alloy bone implants does not match that of bone tissue, which can easily cause stress shielding and lead to atrophy and absorption of alveolar bone. Chitosan hydrogel scaffolds are an important method to solve soft tissue repair, but biological scaffolds made of hydrogels have problems such as insufficient strength and are not suitable for the repair of hard tissues in load-bearing areas. In addition, the surface of the implant lacks periodontal membrane-like structures and a repair microenvironment, making it impossible to effectively bridge the implant and the alveolar bone, which leads to repair failure. Summary of the invention
[0003] The present invention aims to solve the problem that the elastic modulus of existing titanium alloy implants does not match that of bone tissue and lacks a repair microenvironment, which easily leads to repair failure, and further provides a method for constructing a bionic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium.
[0004] 1. 3D printed porous titanium stent:
[0005] The porous titanium stent is prepared by using 3D printing technology, and then the porous titanium stent is surface treated by using concentrated phosphoric acid to obtain a porous titanium stent treated with phosphoric acid;
[0006] 2. Preparation of zinc hydroxyapatite coating on the surface of porous titanium stent:
[0007] The porous titanium stent treated with phosphoric acid is used as an anode and a stainless steel plate is used as a cathode, and then placed in a micro-arc oxidation electrolyte containing an active ingredient, and micro-arc oxidation is performed in a constant voltage mode to obtain a porous titanium stent with a micro-arc oxidation coating on the surface, and the porous titanium stent with the micro-arc oxidation coating on the surface is placed in a microwave hydrothermal solution containing an active ingredient for microwave hydrothermal reaction to obtain a porous titanium stent covered with a zinc-containing hydroxyapatite nanowire coating;
[0008] The micro-arc oxidation electrolyte containing active ingredients is prepared by mixing deionized water, disodium ethylenediaminetetraacetate, sodium hydroxide, sodium silicate, calcium dihydrogen phosphate and calcium acetate;
[0009] The microwave hydrothermal solution containing active ingredients is composed of a mixture of ZnCl2, Zn(OH)2, CaCl2 and deionized water;
[0010] 3. Preparation of chitosan hydrogel:
[0011] ① Under stirring conditions, chitosan is added to water, and then glacial acetic acid is added dropwise, stirred until the chitosan is dissolved, and then heated and methacrylic anhydride is added to react to obtain a methacrylated chitosan precursor;
[0012] ② Add anhydrous ethanol to the methacryloyl chitosan precursor, then adjust the pH to 13-14, filter to obtain solid A, dissolve solid A with hydrochloric acid at a concentration of 0.1 mol / L-0.5 mol / L, then add anhydrous ethanol, adjust the pH to 13-14, filter to obtain solid B, dissolve solid B with hydrochloric acid at a concentration of 0.1 mol / L-0.5 mol / L, adjust the pH to 7, and finally perform dialysis and vacuum freeze drying to obtain methacryloyl chitosan;
[0013] ③ Add pure water to the methacrylylated chitosan, stir and dissolve at a constant temperature to obtain a methacrylylated chitosan solution, then add a photoinitiator and stir, and stand in a dark place until the bubbles disappear to obtain a methacrylylated chitosan hydrogel;
[0014] 4. Preparation of functionalized composite scaffolds:
[0015] A porous titanium scaffold coated with zinc-containing hydroxyapatite nanowires is immersed in methacrylated chitosan hydrogel and finally cured by ultraviolet light to obtain a chitosan hydrogel-coupled porous titanium biomimetic tissue engineering scaffold with excellent biological activity.
[0016] The beneficial effects of the present invention are:
[0017] The present invention is based on a 3D printed porous titanium scaffold, and after micro-arc oxidation and microwave hydrothermal activation treatment, combined with UV curable methacrylic chitosan hydrogel, it can not only match the elastic modulus of bone tissue, but also induce new bone formation, and provide an antibacterial repair microenvironment. Among them, the 3D printed porous titanium skeleton provides structural strength, the UV cross-linked chitosan hydrogel imitates the repair microenvironment, and the chitosan hydrogel forms a good combination with the porous titanium skeleton. There are abundant porous structures inside the hydrogel, which have a similar structure to cells and have the function of inducing cell growth. The hydrogel gradually degrades in the biological fluid environment, can act as a release medium, realize the gradual release of calcium elements in the coating, and induce the formation of bone-like apatite. After coupling the UV cross-linked chitosan hydrogel with the active porous titanium scaffold, SEM analysis shows that the hydrogel has a three-dimensional reticular structure, and the hydrogel is highly filled in the porous titanium scaffold. And the calcium and phosphorus elements in the coating can be slowly released into the simulated body fluid to achieve the role of a sustained-release medium. The present invention combines UV cross-linked chitosan hydrogel with highly active 3D printed porous titanium implants for the first time. In vitro simulated body fluid immersion tests show that the bionic tissue engineering scaffold exhibits excellent biological activity. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a scanned photo of the methacrylylated chitosan hydrogel prepared in step 3 of Example 1 after curing;
[0019] Figure 2 This is a scanned photo of a porous titanium stent coated with zinc-containing hydroxyapatite nanowires prepared in step 2 of Example 1;
[0020] Figure 3 This is a scanned photo of the chitosan hydrogel coupled with porous titanium to construct a biomimetic tissue engineering scaffold with excellent biological activity prepared in step 4 of Example 1;
[0021] Figure 4 The release diagram of calcium in CS-MH, MAO and MH prepared in Example 1 and Comparative Experiments 1 to 2;
[0022] Figure 5 The SEM photo and EDS spectrum of the chitosan hydrogel-coupled porous titanium prepared in step 4 of Example 1 to construct a biomimetic tissue engineering scaffold with excellent bioactivity after being immersed in simulated body fluid for 14 days;
[0023] Figure 6 This is a scanning electron microscope image of the porous titanium scaffold after phosphoric acid treatment prepared in step 1 of Example 1;
[0024] Figure 7 This is an EDS spectrum photograph of the coating layer of the porous titanium stent coated with zinc-containing hydroxyapatite nanowire coating prepared in step 2 of Example 1;
[0025] Figure 8 These are the 3D reconstruction results and scanned photos of the in vivo implantation experiment of the chitosan hydrogel coupled with porous titanium to construct a bionic tissue engineering scaffold with excellent bioactivity prepared in step 4 of Example 1. DETAILED DESCRIPTION
[0026] Specific implementation method 1: This implementation method is a method for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium, which is carried out according to the following steps:
[0027] 1. 3D printed porous titanium stent:
[0028] The porous titanium stent is prepared by using 3D printing technology, and then the porous titanium stent is surface treated by using concentrated phosphoric acid to obtain a porous titanium stent treated with phosphoric acid;
[0029] 2. Preparation of zinc hydroxyapatite coating on the surface of porous titanium stent:
[0030] The porous titanium stent treated with phosphoric acid is used as an anode and a stainless steel plate is used as a cathode, and then placed in a micro-arc oxidation electrolyte containing an active ingredient, and micro-arc oxidation is performed in a constant voltage mode to obtain a porous titanium stent with a micro-arc oxidation coating on the surface, and the porous titanium stent with the micro-arc oxidation coating on the surface is placed in a microwave hydrothermal solution containing an active ingredient for microwave hydrothermal reaction to obtain a porous titanium stent covered with a zinc-containing hydroxyapatite nanowire coating;
[0031] The micro-arc oxidation electrolyte containing active ingredients is prepared by mixing deionized water, disodium ethylenediaminetetraacetate, sodium hydroxide, sodium silicate, calcium dihydrogen phosphate and calcium acetate;
[0032] The microwave hydrothermal solution containing active ingredients is composed of a mixture of ZnCl2, Zn(OH)2, CaCl2 and deionized water;
[0033] 3. Preparation of chitosan hydrogel:
[0034] ① Under stirring conditions, chitosan is added to water, and then glacial acetic acid is added dropwise, stirred until the chitosan is dissolved, and then heated and methacrylic anhydride is added to react to obtain a methacrylated chitosan precursor;
[0035] ② Add anhydrous ethanol to the methacryloyl chitosan precursor, then adjust the pH to 13-14, filter to obtain solid A, dissolve solid A with hydrochloric acid at a concentration of 0.1 mol / L-0.5 mol / L, then add anhydrous ethanol, adjust the pH to 13-14, filter to obtain solid B, dissolve solid B with hydrochloric acid at a concentration of 0.1 mol / L-0.5 mol / L, adjust the pH to 7, and finally perform dialysis and vacuum freeze drying to obtain methacryloyl chitosan;
[0036] ③ Add pure water to the methacrylylated chitosan, stir and dissolve at a constant temperature to obtain a methacrylylated chitosan solution, then add a photoinitiator and stir, and stand in a dark place until the bubbles disappear to obtain a methacrylylated chitosan hydrogel;
[0037] 4. Preparation of functionalized composite scaffolds:
[0038] A porous titanium scaffold coated with zinc-containing hydroxyapatite nanowires is immersed in methacrylated chitosan hydrogel and finally cured by ultraviolet light to obtain a chitosan hydrogel-coupled porous titanium biomimetic tissue engineering scaffold with excellent biological activity.
[0039] The beneficial effects of this embodiment are:
[0040] This embodiment is based on the 3D printed porous titanium scaffold, and after micro-arc oxidation and microwave hydrothermal activation treatment, combined with UV-curable methacryloyl chitosan hydrogel, it can not only match the elastic modulus of bone tissue, but also induce new bone formation, and provide an antibacterial repair microenvironment. Among them, the 3D printed porous titanium skeleton provides structural strength, the UV cross-linked chitosan hydrogel imitates the repair microenvironment, and the chitosan hydrogel forms a good combination with the porous titanium skeleton. There are abundant porous structures inside the hydrogel, which have a similar structure to cells and have the function of inducing cell growth. The hydrogel gradually degrades in the biological fluid environment and can act as a release medium to achieve the gradual release of calcium elements in the coating and induce the formation of bone-like apatite. After coupling the UV cross-linked chitosan hydrogel with the active porous titanium scaffold, SEM analysis shows that the hydrogel has a three-dimensional network structure, and the hydrogel is highly filled in the porous titanium scaffold. And the calcium and phosphorus elements in the coating can be slowly released into the simulated body fluid to achieve the role of a sustained-release medium. This embodiment combines UV cross-linked chitosan hydrogel with highly active 3D printed porous titanium implants for the first time, and in vitro simulated body fluid immersion tests show that the bionic tissue engineering scaffold exhibits excellent biological activity.
[0041] Specific implementation method 2: This implementation method is different from specific implementation method 1 in that: the material of the porous titanium stent described in step 1 is titanium, TA2, TA3, TA4, TC4 or Ti2448; the surface treatment of the porous titanium stent using concentrated phosphoric acid in step 1 is specifically carried out according to the following steps: the porous titanium stent is immersed in a concentrated phosphoric acid solution with a mass percentage of 40% to 75%, and then treated at a temperature of 60°C to 80°C for 10min to 60min. The rest is the same as specific implementation method 1.
[0042] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the diameter of the connecting rod in the porous titanium stent described in step one is 150 μm to 450 μm, and the pore size is 400 μm to 900 μm; the pore unit in the porous titanium stent described in step one is one of a square structure, a diamond structure and a regular dodecahedron structure or a combination of several thereof; the porosity of the porous titanium stent described in step one is 40% to 60%. Others are the same as specific implementation method one or two.
[0043] Specific embodiment 4: This embodiment is different from specific embodiments 1 to 3 in that: the micro-arc oxidation described in step 2 is specifically treated for 5min to 15min under the conditions of voltage of 400V to 500V, pulse frequency of 600Hz to 1000Hz, duty cycle of 4% to 20% and electrolyte temperature of 20℃ to 30℃; the microwave hydrothermal reaction described in step 2 is specifically heated to 160℃ to 200℃ at a heating rate of 5℃ / min to 20℃ / min, and then treated for 15min to 60min at a temperature of 160℃ to 200℃ and a power of 400W to 1200W. Others are the same as specific embodiments 1 to 3.
[0044] Specific embodiment 5: This embodiment is different from the specific embodiments 1 to 4 in that: the concentration of disodium ethylenediaminetetraacetate in the micro-arc oxidation electrolyte containing active ingredients described in step 2 is 5g / L to 40g / L, the concentration of sodium hydroxide is 5g / L to 20g / L, the concentration of sodium silicate is 2g / L to 15g / L, the concentration of calcium dihydrogen phosphate is 5g / L to 25g / L, and the concentration of calcium acetate is 5g / L to 30g / L; the concentration of ZnCl2 in the microwave hydrothermal solution containing active ingredients described in step 2 is 0.01mol / L to 3.0mol / L, the molar ratio of ZnCl2 to Zn(OH)2 is 1:(1 to 3), and the molar ratio of ZnCl2 to CaCl2 is 1:(2 to 3); the microwave hydrothermal solution containing active ingredients described in step 2 is adjusted to pH 1 to 7 by hydrochloric acid with a mass percentage of 10% to 37%. Others are the same as specific embodiments 1 to 4.
[0045] Specific embodiment 6: This embodiment is different from the specific embodiments 1 to 5 in that: the volume ratio of the mass of chitosan described in step 3 ① to water is 1g: (90-99) mL; the volume ratio of the mass of chitosan described in step 3 ① to glacial acetic acid is 1g: (0.5-2.0) mL; the molar ratio of the amino group of chitosan described in step 3 ① to the anhydride group of methacrylic anhydride is 1: (1-5); step 3 ① is heated to a temperature of 20°C to 60°C, and then methacrylic anhydride is added, and the reaction is carried out at a temperature of 20°C to 60°C for 3h to 12h. The rest is the same as the specific embodiments 1 to 5.
[0046] Specific embodiment seven: This embodiment is different from any one of specific embodiments one to six in that: the mass ratio of the methacryloyl chitosan precursor described in step three ② to anhydrous ethanol is 1g:(100-500)mL; the mass ratio of the solid A described in step three ② to hydrochloric acid with a concentration of 0.1mol / L-0.5mol / L is 1g:(10-50)mL; the mass ratio of the solid A described in step three ② to anhydrous ethanol is 1g:(100-500)mL; the mass ratio of the solid B described in step three ② to hydrochloric acid with a concentration of 0.1mol / L-0.5mol / L is 1g:(10-50)mL; in step three ②, a 10%-80% by mass NaOH solution is used to adjust the pH to 13-14; in step three ②, a 10%-50% by mass sodium bicarbonate solution or a 10%-50% by mass sodium carbonate solution is used to adjust the pH to 7. The rest is the same as Specific Embodiments 1 to 6.
[0047] Specific embodiment 8: This embodiment differs from specific embodiments 1 to 7 in that: the dialysis described in step 3 ② is specifically performed using a dialysis bag with a dialysis molecular weight of 8000 to 12000 in a deionized water environment for 12 to 72 hours; the vacuum freeze drying described in step 3 ② is specifically performed at a temperature of -196°C to -150°C for 6 to 24 hours. The rest is the same as specific embodiments 1 to 7.
[0048] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: the mass percentage of methacrylylated chitosan in the methacrylylated chitosan solution described in step 3 ③ is 0.5% to 2.5%; the constant temperature stirring and dissolving in step 3 ③ is specifically stirred for 0.5h to 3h at a speed of 1000rpm to 3000rpm and a water bath temperature of 20℃ to 50℃; the photoinitiator described in step 3 ③ is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; the mass of the photoinitiator described in step 3 ③ is 0.5‰ to 1.5‰ of the mass of the methacrylylated chitosan solution; the photoinitiator is added in step 3 ③, and stirred for 0.5h to 3h at a speed of 500rpm to 2500rpm. The rest is the same as specific embodiments 1 to 8.
[0049] Specific embodiment 10: This embodiment differs from specific embodiments 1 to 9 in that the UV curing described in step 4 is specifically carried out at a wavelength of 300nm to 760nm and a power of 200mW / cm 2 ~400mW / cm 2 Under the condition of , UV curing for 30s to 90s. The rest is the same as the specific embodiments 1 to 9.
[0050] The following examples are used to verify the beneficial effects of the present invention:
[0051] Embodiment 1:
[0052] A method for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium is carried out according to the following steps:
[0053] 1. 3D printed porous titanium stent:
[0054] The porous titanium stent is prepared by using 3D printing technology, and then the porous titanium stent is surface treated by using concentrated phosphoric acid to obtain a porous titanium stent treated with phosphoric acid;
[0055] 2. Preparation of zinc hydroxyapatite coating on the surface of porous titanium stent:
[0056] The porous titanium stent treated with phosphoric acid is used as an anode and a stainless steel plate is used as a cathode, and then placed in a micro-arc oxidation electrolyte containing an active ingredient, and micro-arc oxidation is performed in a constant voltage mode to obtain a porous titanium stent with a micro-arc oxidation coating on the surface, and the porous titanium stent with the micro-arc oxidation coating on the surface is placed in a microwave hydrothermal electrolyte containing an active ingredient for microwave hydrothermal reaction to obtain a porous titanium stent covered with a zinc-containing hydroxyapatite nanowire coating;
[0057] The micro-arc oxidation electrolyte containing active ingredients is prepared by mixing deionized water, disodium ethylenediaminetetraacetate, sodium hydroxide, sodium silicate, calcium dihydrogen phosphate and calcium acetate;
[0058] The microwave hydrothermal electrolyte containing active ingredients is composed of a mixture of ZnCl2, Zn(OH)2, CaCl2 and deionized water;
[0059] 3. Preparation of chitosan hydrogel:
[0060] ① Under stirring conditions, chitosan is added to water, and then glacial acetic acid is added dropwise, stirred until the chitosan is dissolved, and then heated and methacrylic anhydride is added to react to obtain a methacrylated chitosan precursor;
[0061] ② Add anhydrous ethanol to the methacryloyl chitosan precursor, then adjust the pH to 13, filter to obtain solid A, dissolve solid A with 0.5 mol / L hydrochloric acid, then add anhydrous ethanol, adjust the pH to 13, filter to obtain solid B, dissolve solid B with 0.5 mol / L hydrochloric acid, adjust the pH to 7, and finally perform dialysis and vacuum freeze-drying to obtain methacryloyl chitosan;
[0062] ③ Add pure water to the methacrylylated chitosan, stir and dissolve at a constant temperature to obtain a methacrylylated chitosan solution, then add a photoinitiator and stir, and stand in a dark place until the bubbles disappear to obtain a methacrylylated chitosan hydrogel;
[0063] 4. Preparation of functionalized composite scaffolds:
[0064] The porous titanium scaffold coated with zinc-containing hydroxyapatite nanowires was immersed in methacrylated chitosan hydrogel and finally UV-cured to obtain a chitosan hydrogel-coupled porous titanium biomimetic tissue engineering scaffold with excellent bioactivity, named CS-MH.
[0065] The material of the porous titanium stent described in step one is TA2; in step one, the porous titanium stent is surface treated with concentrated phosphoric acid, specifically according to the following steps: the porous titanium stent is immersed in a concentrated phosphoric acid solution with a mass percentage of 75%, and then treated at a temperature of 80°C for 30 minutes.
[0066] The connecting rod in the porous titanium stent described in step one is cylindrical, with a diameter of 400 μm and a pore size of 640 μm; the size of the porous titanium stent described in step one is 10 mm×10 mm×4 mm, and the pore unit is a diamond structure; the porosity of the porous titanium stent described in step one is 60%.
[0067] The micro-arc oxidation described in step 2 is specifically carried out at a voltage of 450V, a pulse frequency of 600Hz, a duty cycle of 8% and an electrolyte temperature of 20°C for 5min; the microwave hydrothermal reaction described in step 2 is specifically carried out at a heating rate of 10°C / min to 200°C, and then at a temperature of 200°C and a power of 800W for 60min.
[0068] The concentration of disodium ethylenediaminetetraacetate in the micro-arc oxidation electrolyte containing active ingredients described in step 2 is 15 g / L, the concentration of sodium hydroxide is 5 g / L, the concentration of sodium silicate is 7.1 g / L, the concentration of calcium dihydrogen phosphate is 6.3 g / L, and the concentration of calcium acetate is 8.8 g / L; the concentration of ZnCl2 in the microwave hydrothermal electrolyte containing active ingredients in step 2 is 0.5 mol / L, the molar ratio of ZnCl2 to Zn(OH)2 is 1:1, and the molar ratio of ZnCl2 to CaCl2 is 1:2; the pH of the microwave hydrothermal solution containing active ingredients described in step 2 is adjusted to 7 by 37% by mass hydrochloric acid.
[0069] The mass ratio of chitosan described in step 3① to water is 1g:99mL; the mass ratio of chitosan described in step 3① to glacial acetic acid is 1g2.0mL; the molar ratio of the amino group of chitosan described in step 3① to the anhydride group of methacrylic anhydride is 1:2; step 3① is heated to a temperature of 60°C, and then methacrylic anhydride is added, and the reaction is carried out at a temperature of 60°C for 12h.
[0070] The mass ratio of the methacryloyl chitosan precursor described in step 3② to anhydrous ethanol is 1g:300mL; the mass ratio of the solid A described in step 3② to 0.5mol / L hydrochloric acid is 1g:20mL; the mass ratio of the solid A described in step 3② to anhydrous ethanol is 1g:300mL; the mass ratio of the solid B described in step 3② to 0.5mol / L hydrochloric acid is 1g:20mL; in step 3②, the pH is adjusted to 13 using a 20% mass percentage NaOH solution; in step 3②, the pH is adjusted to 7 using a 30% mass percentage sodium bicarbonate solution.
[0071] The dialysis described in step 3② is specifically performed using a dialysis bag with a dialysis molecular weight of 10,000 in a deionized water environment for 48 hours; the vacuum freeze-drying described in step 3② is specifically performed at a temperature of -196°C and vacuum freeze-drying for 24 hours.
[0072] The mass percentage of methacryloyl chitosan in the methacryloyl chitosan solution described in step 3③ is 2.5%; the constant temperature stirring and dissolving in step 3③ is specifically stirred for 3 hours at a speed of 2500rpm and a water bath temperature of 30°C; the photoinitiator described in step 3③ is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; the mass of the photoinitiator described in step 3③ is 1.5‰ of the mass of the methacryloyl chitosan solution; the photoinitiator is added in step 3③ and stirred for 30 minutes at a speed of 2000rpm.
[0073] The UV curing described in step 4 is specifically performed at a wavelength of 365nm and a power of 400mW / cm 2 Under the conditions of UV curing for 30s.
[0074] Comparative Experiment 1: This comparative experiment is different from Example 1 in that only the micro-arc oxidation treatment in Step 1 and Step 2 is performed to obtain a porous titanium stent with a micro-arc oxidation coating on the surface, named MAO. The rest is the same as Example 1.
[0075] Comparative Experiment 2: This comparative experiment is different from Example 1 in that only Step 1 and Step 2 are performed, and a porous titanium stent coated with zinc-containing hydroxyapatite nanowire coating is obtained in Step 2, which is named MH. The rest is the same as Example 1.
[0076] The elastic modulus of the porous titanium stent prepared in step 1 of example 1 is 4.4 GPa.
[0077] The methacryloyl chitosan hydrogel prepared in step 3 of Example 1 was heated at a wavelength of 365 nm and a power of 400 mW / cm 2 Under the conditions of UV curing for 30s, and then the scanning electron microscope test was carried out. Figure 1 This is a scanned photo of the methacrylylated chitosan hydrogel prepared in step 3 of Example 1 after curing; as can be seen from the figure, the UV cross-linked chitosan hydrogel has a loose porous structure.
[0078] Figure 2 This is a scanned photo of the porous titanium stent coated with zinc-containing hydroxyapatite nanowires prepared in step 2 of Example 1; as can be seen from the figure, a large number of zinc-doped hydroxyapatite nanowires are formed on the surface of the porous titanium stent, with a diameter of about 100 nm and a length of approximately 50 nm.
[0079] Figure 3 This is a scanned photo of the chitosan hydrogel coupled with porous titanium to construct a biomimetic tissue engineering scaffold with excellent bioactivity prepared in step 4 of Example 1; as can be seen from the figure, the UV cross-linked chitosan hydrogel forms a good combination with the porous titanium scaffold, showing a high degree of filling.
[0080] In order to avoid the influence of calcium and phosphate ions in simulated body fluids, PBS solution was selected as the soaking solution. After CS-MH, MAO and MH were soaked in PBS solution at 37°C for different periods of time, samples were taken and calcium ion release concentration was detected using ICP-OES. Figure 4 The release diagram of calcium in CS-MH, MAO and MH prepared in Example 1 and Comparative Experiments 1 to 2 shows that, compared with MAO and MH samples, the release rate of calcium ions in the bionic tissue engineering scaffold CS-MH is the lowest, with a degradation rate of 20 μg / day. As the hydrogel degrades, the release rate increases, indicating that the chitosan hydrogel plays a sustained release role.
[0081] Figure 5 The SEM photograph and EDS energy spectrum diagram of the chitosan hydrogel-coupled porous titanium constructed biomimetic tissue engineering scaffold with excellent bioactivity prepared in step 4 of Example 1 after being immersed in simulated body fluid for 14 days; as can be seen from the figure, at a temperature of 37°C, the composite scaffold was immersed in simulated body fluid for 14 days, and a large amount of apatite was produced in the chitosan hydrogel area and was close to saturation.
[0082] The contents of the simulated body fluid components described in Example 1 are shown in Table 1:
[0083] Table 1 Chemical reagent content of 1L simulated body fluid
[0084]
[0085] Figure 6 This is a scanning electron microscope image of the porous titanium stent after phosphoric acid treatment prepared in step 1 of Example 1; it can be seen from the figure that after phosphoric acid corrosion, a large number of micron-scale corrosion pit structures are formed on the surface, with a size of approximately 1μm to 3μm; the pore size of the porous titanium stent is approximately 640μm, and the diameter of the porous titanium stent connecting rod is approximately 400μm.
[0086] Figure 7 This is an EDS spectrum photo of the coating layer of the porous titanium stent coated with zinc-containing hydroxyapatite nanowires prepared in step 2 of Example 1. As can be seen from the figure, the coating layer is mainly composed of titanium, oxygen, calcium, phosphorus and zinc elements, indicating that the zinc element has been successfully introduced after the hydrothermal treatment.
[0087] First, a defect model with a diameter of 2 mm and a length of 6 mm was processed on the tibia of a New Zealand white rabbit using a special tool for animal experiment processing, and then the chitosan hydrogel coupled with porous titanium prepared in step 4 of Example 1 to construct a bionic tissue engineering scaffold with excellent bioactivity was implanted into the defect position. After 8 weeks of implantation, the rabbit was killed, the tibia with the implant was taken out, and then the new bone tissue was characterized and analyzed using a three-dimensional X-ray microscope and a scanning electron microscope; Figure 8 The 3D reconstruction results and scanned photos of the in vivo implantation experiment of the chitosan hydrogel coupled with porous titanium to construct a biomimetic tissue engineering scaffold with excellent bioactivity prepared in step 4 of Example 1. As can be seen from the figure, new bone tissue has grown on the surface and in the pores of the biomimetic tissue engineering scaffold, and the surface has excellent new bone induction regeneration ability.
Claims
1. A method for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium, characterized in that It is carried out in the following steps:
1. 3D printed porous titanium stent: The porous titanium stent is prepared by using 3D printing technology, and then the porous titanium stent is surface treated by using concentrated phosphoric acid to obtain a porous titanium stent treated with phosphoric acid; 2. Preparation of zinc hydroxyapatite coating on the surface of porous titanium stent: The porous titanium stent treated with phosphoric acid is used as an anode and a stainless steel plate is used as a cathode, and then placed in a micro-arc oxidation electrolyte containing an active ingredient, and micro-arc oxidation is performed in a constant voltage mode to obtain a porous titanium stent with a micro-arc oxidation coating on the surface, and the porous titanium stent with the micro-arc oxidation coating on the surface is placed in a microwave hydrothermal solution containing an active ingredient for microwave hydrothermal reaction to obtain a porous titanium stent covered with a zinc-containing hydroxyapatite nanowire coating; The micro-arc oxidation electrolyte containing active ingredients is prepared by mixing deionized water, disodium ethylenediaminetetraacetate, sodium hydroxide, sodium silicate, calcium dihydrogen phosphate and calcium acetate; The microwave hydrothermal solution containing active ingredients is composed of a mixture of ZnCl2, Zn(OH)2, CaCl2 and deionized water; 3. Preparation of chitosan hydrogel: ① Under stirring conditions, chitosan is added to water, and then glacial acetic acid is added dropwise, stirred until the chitosan is dissolved, and then heated and methacrylic anhydride is added to react to obtain a methacrylated chitosan precursor; ② Add anhydrous ethanol to the methacryloyl chitosan precursor, then adjust the pH to 13-14, filter to obtain solid A, dissolve solid A with hydrochloric acid at a concentration of 0.1 mol / L-0.5 mol / L, then add anhydrous ethanol, adjust the pH to 13-14, filter to obtain solid B, dissolve solid B with hydrochloric acid at a concentration of 0.1 mol / L-0.5 mol / L, adjust the pH to 7, and finally perform dialysis and vacuum freeze drying to obtain methacryloyl chitosan; ③ Add pure water to the methacrylylated chitosan, stir and dissolve at a constant temperature to obtain a methacrylylated chitosan solution, then add a photoinitiator and stir, and stand in a dark place until the bubbles disappear to obtain a methacrylylated chitosan hydrogel; 4. Preparation of functionalized composite scaffolds: A porous titanium scaffold coated with zinc-containing hydroxyapatite nanowires is immersed in methacrylated chitosan hydrogel and finally cured by ultraviolet light to obtain a chitosan hydrogel-coupled porous titanium biomimetic tissue engineering scaffold with excellent biological activity.
2. The method for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium according to claim 1, characterized in that The material of the porous titanium bracket described in step one is titanium, TA2, TA3, TA4, TC4 or Ti2448; the surface treatment of the porous titanium bracket using concentrated phosphoric acid in step one is specifically carried out according to the following steps: immersing the porous titanium bracket in a concentrated phosphoric acid solution with a mass percentage of 40% to 75%, and then treating it at a temperature of 60°C to 80°C for 10min to 60min.
3. The method for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium according to claim 1, characterized in that The connecting rod diameter of the porous titanium scaffold described in step one is 150μm to 450μm, and the pore size is 400μm to 900μm; the porous titanium scaffold described in step one has a pore unit of a square structure, a diamond structure and a regular dodecahedron structure or a combination of several thereof; the porosity of the porous titanium scaffold described in step one is 40% to 60%.
4. The method of constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium according to claim 1, characterized in that The micro-arc oxidation described in step 2 is specifically carried out under the conditions of a voltage of 400V to 500V, a pulse frequency of 600Hz to 1000Hz, a duty cycle of 4% to 20% and an electrolyte temperature of 20°C to 30°C, and the treatment is carried out for 5min to 15min; the microwave hydrothermal reaction described in step 2 is specifically carried out at a heating rate of 5°C / min to 20°C / min to 160°C to 200°C, and then at a temperature of 160°C to 200°C and a power of 400W to 1200W, and the treatment is carried out for 15min to 60min.
5. The method for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium according to claim 1, characterized in that The concentration of disodium ethylenediaminetetraacetate in the micro-arc oxidation electrolyte containing active ingredients described in step 2 is 5g / L~40g / L, the concentration of sodium hydroxide is 5g / L~20g / L, the concentration of sodium silicate is 2g / L~15g / L, the concentration of calcium dihydrogen phosphate is 5g / L~25g / L, and the concentration of calcium acetate is 5g / L~30g / L; the concentration of ZnCl2 in the microwave hydrothermal solution containing active ingredients described in step 2 is 0.01mol / L~3.0mol / L, the molar ratio of ZnCl2 to Zn(OH)2 is 1:(1~3), and the molar ratio of ZnCl2 to CaCl2 is 1:(2~3); the pH of the microwave hydrothermal solution containing active ingredients described in step 2 is adjusted to 1~7 by 10%~37% by mass hydrochloric acid.
6. The method of claim 1 for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium, characterized in that The mass ratio of chitosan described in step 3① to water is 1g:(90-99)mL; the mass ratio of chitosan described in step 3① to glacial acetic acid is 1g:(0.5-2.0)mL; the molar ratio of the amino group of chitosan described in step 3① to the anhydride group of methacrylic anhydride is 1:(1-5); step 3① is heated to a temperature of 20℃-60℃, and then methacrylic anhydride is added, and the reaction is carried out at a temperature of 20℃-60℃ for 3h-12h.
7. The method of claim 1 for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium, characterized in that The mass ratio of the methacryloyl chitosan precursor described in step 3② to the volume ratio of anhydrous ethanol is 1g:(100-500)mL; the mass ratio of the solid A described in step 3② to the volume ratio of hydrochloric acid with a concentration of 0.1mol / L-0.5mol / L is 1g:(10-50)mL; the mass ratio of the solid A described in step 3② to anhydrous ethanol is 1g:(100-500)mL; the mass ratio of the solid B described in step 3② to the volume ratio of hydrochloric acid with a concentration of 0.1mol / L-0.5mol / L is 1g:(10-50)mL; in step 3②, the pH is adjusted to 13-14 using a 10%-80% NaOH solution by mass; in step 3②, the pH is adjusted to 7 using a 10%-50% sodium bicarbonate solution by mass or a 10%-50% sodium carbonate solution by mass.
8. The method of claim 1 for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium, characterized in that The dialysis described in step 3② is specifically performed using a dialysis bag with a dialysis molecular weight of 8000 to 12000 in a deionized water environment for 12h to 72h; the vacuum freeze-drying described in step 3② is specifically performed at a temperature of -196°C to -150°C for 6h to 24h.
9. The method of claim 1 for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium, characterized in that The mass percentage of methacryloyl chitosan in the methacryloyl chitosan solution described in step 3③ is 0.5% to 2.5%; the constant temperature stirring and dissolving in step 3③ is specifically stirred for 0.5h to 3h at a rotation speed of 1000rpm to 3000rpm and a water bath temperature of 20°C to 50°C; the photoinitiator described in step 3③ is 2-hydroxy-4'-(2-hydroxyethoxy)-2-methylpropiophenone; the mass of the photoinitiator described in step 3③ is 0.5‰ to 1.5‰ of the mass of the methacryloyl chitosan solution; the photoinitiator is added in step 3③, and stirred for 0.5h to 3h at a rotation speed of 500rpm to 2500rpm.
10. The method of claim 1 for constructing a biomimetic tissue engineering scaffold with excellent biological activity by coupling chitosan hydrogel with porous titanium, characterized in that The UV curing described in step 4 is specifically performed at a wavelength of 300nm to 760nm and a power of 200mW / cm 2 ~400mW / cm 2 Under the conditions of UV curing for 30s to 90s.